Tanggung Jawab Hukum Perusahaan Terhadap Kerugian Yang Diderita Konsumen Akibat Produk Cacat - Deswari, Meissy Putri; Sucia, Yossiramah; Fikrina, Aulia (-, 2025)
Many countries already have laws to regulate consumer protection, but in reality there are still many companies that do not comply with legal obligations related to product safety and quality standards. This study aims to explore the extent of corporate legal responsibility in dealing with claims for losses due to defective products. The method used in writing this scientific paper uses a literature study research method with a qualitative approach. In Indonesia, consumer protection is regulated in Law Number 8 of 1999 concerning Consumer Protection (Consumer Protection Law). This law provides a strong legal basis for consumers to get compensation if they are harmed due to defective products. Consumers who feel disadvantaged due to defective products can submit a claim for compensation to business actors. In addition, the company is also expected to take preventive measures so that similar incidents do not recur.